Ensuring the Safety of Gas Distribution Stations When Increasing Capacity. Issue 7 (March 2021) - Fomina, E; Guskov, M; Mitichkin, S; Shishkin, S
Abstract: The paper shows the dynamics of accidents and industrial fatality injuries at the Main Pipeline Transport of Hydrocarbons in the Russian Federation. The features of operation of a Gas Distribution Station (GDS) as one of the Hazardous Production Facilities of Main Pipeline Transport of Natural Gas are considered. The main technological units and systems for ensuring the complex safety of automated low-performance GDS are presented. The main factors contributing to the occurrence and development of accidents at the GDS are listed. To increase gas supplies to the consumer, the calculation of the technically possible throughput capacity of the existing GDS with a design capacity of 20 thousand m 3 /hour was carried out. Using a software complex "Vesta-GDS" we built process flow diagram that under the given constraints (pressure, temperature, gas velocity in the pipeline and the degree of opening of the gas pressure regulator valve) determined that the technically possible throughput capacity of GDS is 16.37 thousand m 3 /hour more than design capacity. With technically possible increased productivity, a qualitative and quantitative assessment of the risk of an accident at the GDS II class of danger was made, as a result of which the risk was assessed as "low" and not exceeding the background indicators of the oil and gas industry of the Russian Federation.